Pengembangan Potensi Kawasan Wisata Kota Tua di Kota Padang - Aulia Rahman; Muhammad Ichsan; Kusdarini (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik (J-EMSPOL), 2025)
This study aims to describe how to develop the tourism potential of the old town in Padang City. The development of this tourism potential is also expected to be able to improve the regional economy and society. The theory of elements of this development uses the theory by Cooper with 4A namely Attraction, Amenity, Accessibility, and Ancillary. The method used in this study is a qualitative descriptive method using data collection techniques through interviews, observation, and documentation while the informant selection technique uses a purposive sampling technique. Then in testing the validity of the data researchers used source triangulation. Based on the methods and research conducted, it was found that the development of the Kota Tua tourism potential in Padang City was not optimal. This is obtained from the results of the variables carried out during the study.